2003
DOI: 10.1001/archneur.60.10.1421
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Phenotypes in Patients With Facioscapulohumeral Muscular Dystrophy 4q35 Deletion

Abstract: The clinical presentations in patients with FSHD-associated short fragments on chromosome 4q35 are not restricted to the classic FSHD form, but constitute a variety of clinical manifestations. There seems to be no clear correlation between the atypical subtype and the DNA fragment size due to the deletion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
40
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 12 publications
6
40
0
2
Order By: Relevance
“…Interestingly it has been suggested that patients harboring D4Z4 alleles of ≥35 kb (≥ 8 repeats) were less likely to present the classic FSHD phenotype as compared with patients with alleles of <35 kb (<8 repeats) (Felice and Whitaker, 2005). Several clinical reports described myopathic patients, carrying alleles of 38 kb (9 repeats) or larger, showing typical and atypical FSHD phenotypes (Vitelli et al, 1999;Felice et al, 2000;Felice and Moore, 2001;Butz et al, 2003;Krasnianski et al, 2003). However D4Z4 repeat arrays of size between 38-45 kb (9-11 repeats) were encountered in 3% of 200 control subjects in a Dutch study .…”
Section: Severity Of the Disease And Repeats Number: Does A Linear Comentioning
confidence: 99%
“…Interestingly it has been suggested that patients harboring D4Z4 alleles of ≥35 kb (≥ 8 repeats) were less likely to present the classic FSHD phenotype as compared with patients with alleles of <35 kb (<8 repeats) (Felice and Whitaker, 2005). Several clinical reports described myopathic patients, carrying alleles of 38 kb (9 repeats) or larger, showing typical and atypical FSHD phenotypes (Vitelli et al, 1999;Felice et al, 2000;Felice and Moore, 2001;Butz et al, 2003;Krasnianski et al, 2003). However D4Z4 repeat arrays of size between 38-45 kb (9-11 repeats) were encountered in 3% of 200 control subjects in a Dutch study .…”
Section: Severity Of the Disease And Repeats Number: Does A Linear Comentioning
confidence: 99%
“…Molecular diagnosis of FSHD broadened the clinical spectrum of this disease, including asymptomatic individuals with minimal clinical signs, patients with predominant distal muscle involvement, patients without facial weakness, FSHD presenting as bent spine syndrome or severe generalized muscle weakness [3]. Therefore, we reevaluated the applicability of Beevor's sign in patients with molecularly-proven FSHD displaying typical and atypical phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Miura et al 8 reported an individual with FSHD and acquired limitation of upgaze, tongue atrophy, and mental retardation. Krasnianski et al 6 described a father and two children with atypical FSHD, confirmed molecularly, with "chronic progressive external ophthalmoplegia" (CPEO). The father developed arm and shoulder-girdle weakness around 25 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…3 Since then, a molecular marker for FSHD has become available, with many diverse phenotypes being recognized in the FSHD clinical spectrum. 6,10 This includes five children originally diagnosed with Möbius syndrome or congenital facial diplegia (albeit with normal extraocular movements) who were later clinically and molecularly confirmed to have FSHD. 2,5 FSHD is caused by a contraction of the macrosatellite repeat D4Z4 on chromosome 4qter.…”
mentioning
confidence: 99%